Insights into the relationship between weather parameters and COVID-19 outbreak in Lombardy, Italy. (2nd January 2021) - Ceylan, Zeynep
ABSTRACT: Meteorological conditions are essential factors affecting the spread of infectious diseases caused by viruses. The aim of this study is to investigate the relationship between the weather parameters and the number of confirmed Corona Virus Disease 2019 (COVID-19) cases in Lombardy, Italy, one of the regions where the first cases in Europe are reported. For this purpose, the reported COVID-19 data between February 20, 2020 and April 21, 2020 was collected from the Italian National Health Ministry website. Besides, daily data on weather conditions of Lombardy were obtained from the Lombardy Regional Agency for Environmental Protection (ARPA Lombardia), which provides a large open data portal to users. The average values of temperature, relative humidity, wind speed, and air pressure were selected as weather parameters. Spearman's rank correlation coefficient test was used to analyze the relationship of weather variables with the COVID-19 outbreak. The analysis results showed that the total number of confirmed COVID-19 cases was positively associated with average temperature ( r  = 0.619). In contrast, a negative correlation was observed with average relative humidity ( r  = −0.371). The results of this study can help decision-makers to create economic and containment policies related to the COVID-19 pandemic.